Aspectos radiológicos en la presencia de aire subdiafragmático de causa no traumática en adultos mayores - Suarez Limones, Dagmar Michelle (Machala : Universidad Técnica de Machala, 2022)
INTRODUCTION: Hollow viscus perforation can be of the gastrointestinal, biliary or genitourinary tract in free form to the cavity, causing generalized peritonitis, that is, as a perforated or partial ulcer; which can lead to localized peritonitis. Its etiology may be due to vascular, traumatic, inflammatory, tumoral, parasitic or idiopathic causes. In this case, the causes that can occur in the case of the presence of subdiaphragmatic air in non-traumatic older adult patients will be exposed. OBJECTIVE: To determine imaging criteria present in hollow viscus perforation of non-traumatic cause in elderly patients, through a literature review in the last 5 years, which allows medical personnel to achieve an effective imaging diagnosis. METHODOLOGY: This is a retrospective descriptive study through a bibliographic review of scientific articles compiled in the scientific bases of SCIELO, PUBMED, MESH, GOOGLE ACADEMIC for the extraction of qualitative information, compiling information on radiological aspects in the presence of subdiaphragmatic air in non-traumatic older adult patients. CONCLUSION: To determine the diagnostic and therapeutic management in the acute abdomen in older adults with suspected presence of air in their diaphragm, it is necessary to assess the patient, if the patient is stable, analgesia is administered with complementary tests and ultrasound images, if this is not conclusively, a computed tomography is requested, once a certainty is obtained regarding the diagnosis, the necessary interconsultations are requested with the corresponding specialty for a multidisciplinary evaluation.
INTRODUCCIÓN: La perforación de víscera hueca puede ser de tracto gastrointestinal, biliar o genitourinario en forma libre a cavidad, provocando peritonitis generalizada, es decir, como úlcera perforada o de forma parcial; que puede desenlazar en una peritonitis localizada. Su etiología puede ser debido a causas vasculares, traumáticas, inflamatorias, tumorales, parasitarias o idiopáticas. En este caso serán expuestas las causas que se pueden presentar ante el caso de presencia de aire subdiafragmático en pacientes adultos mayores no traumáticos. OBJETIVO: Determinar criterios imagenológicos presentes en perforación de víscera hueca de causa no traumática en pacientes adultos mayores, a través de la revisión bibliográfica en los últimos 5 años, que permita al personal médico lograr un diagnóstico por imagen eficaz. METODOLOGÍA: Se trata de un estudio descriptivo retrospectivo a través de una revisión bibliográfica de artículos científicos recopilados en las bases científicas de SCIELO, PUBMED, MESH, GOOGLE ACADÉMICO para extracción de información cualitativa recopilando información de los aspectos radiológicos en la presencia de aire subdiafragmático en pacientes adultos mayores no traumáticos. CONCLUSIÓN: Para determinar el manejo diagnóstico y terapéutico en abdomen agudo en adulto mayor con sospecha de presencia de aire su diafragmático es necesaria la valoración del paciente, si este se encuentra estable se administra analgesia con exámenes complementarios e imágenes de ultrasonido, si este no es concluible se solicita una tomografía computarizada, una vez que se obtiene una certeza ante el diagnostico se solicita las interconsultas necesarias con la especialidad correspondiente para una evaluación multidisciplinaria.
Keywords: AIRE SUBDIAFRAGMATICO; PERFORACION DE VISCERA HUECA; RADIOLOGIA EN PERFORACION DE VISCERA